Light sources of solar simulators for photovoltaic devices: A review. (September 2017) - Esen, Vedat; Sağlam, Şafak; Oral, Bülent
Abstract: As solar power usage is increasing nowadays, performance tests have become one of the most important topics in order to guarantee the security of photovoltaic tools. For photovoltaic panels to become efficient, there is need for health testing of all materials and technologies used in the production of the panels in electrical and optical aspects. Thus, when future energy standards are considered, it is imperative to use solar simulators that obtain near real sunlight spectrum values. The most important components of solar simulators used in photovoltaic panel tests are light sources. In this study, solar simulators were classified based on the light sources they use, and their history and technological development were investigated in line with the literature. Within the scope of this study, carbon arc lamps, sodium vapor lamps, argon arc lamps, quartz-tungsten halogen lamps, mercury xenon lamps, xenon arc, xenon flash lamps, metal halide lamps, LED and super continuum laser light sources were investigated. Additionally, to compare spectral deficiency among these light sources and solar simulators, multiple light sourced solar simulators were also covered under a separate title.